Analisis Peluang Kerja Sama Global dalam Pembiayaan Pembangunan: Studi Pada Utang, Investasi, dan Bantuan Luar Negeri (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study discusses the 17th Sustainable Development Goal (SDG), Partnership for the Goals, which highlights the importance of global collaboration in achieving shared prosperity. The main focus of this research is on three key instruments of global partnership: external debt, foreign investment, and foreign aid. These instruments play a crucial role in supporting development in developing countries, but they also raise controversies related to economic dependence, global power imbalances, and the effectiveness of aid. This study employs a descriptive qualitative approach based on a literature review of international reports and academic research. The analysis shows that although debt, investment, and foreign aid offer opportunities for technology transfer, economic growth, and poverty reduction, their sustainability largely depends on governance, transparency, and equality among nations. Therefore, global partnerships should be directed toward more inclusive and equitable systems to ensure that global development goals can be achieved sustainably.